Abdominal tuberculosis mimicking Crohn's disease's exacerbation: A clinical, diagnostic and surgical dilemma. A case report. (2015) - Papis, Davide; Branchi, Vittorio; Gomez, Luis; Herrerias, Fernando; Vilardell, Felip; Gonzalez, Marta; Olsina, Jorge J
Highlights: Tuberculosis is a health public problem, which has increased over the last 20 years. The diagnosis of extrapulmonary tuberculosis can be challenging, and in particular clinical manifestations of gastrointestinal tuberculosis are unspecific and can mimic other pathologies. Medical therapy is the treatment of choice and surgery is not required if it is diagnosed at an early stage, anyway diagnosis of abdominal tuberculosis still remains a challenge for both internists and surgeons. Before starting a therapy with adalimumab, every patient should be tested for latent tuberculosis infection. Abstract: Introduction: Tuberculosis in Europe is a health public problem, which has increased constantly over the last few decades. The most common clinical manifestation of tuberculosis is pulmonary. The diagnosis of extrapulmonary tuberculosis can be challenging and clinical manifestations of gastrointestinal tuberculosis are unspecific and can mimic other pathologies. Presentation of case: A young Chinese man, who had recently been diagnosed with Crohn's disease, was admitted to the emergency room of our hospital with a one-month history of diffuse abdominal pain and weight loss. The patient initially presented with epigastric pain, which had been constantly increasing over the last 48 h. Other symptoms included diarrhea, nausea, and fever. The patient was then admitted with the diagnosis of Crohn's disease exacerbation, and a treatment with corticosteroids, azathioprine, mesalazine, adalimumab, and antibiotic therapy was started. The symptoms were due to an initially misdiagnosed case of abdominal tuberculosis. Discussion: Intestinal tuberculosis is mainly localized at the ileocecal level in 85% of patients. Medical therapy is the treatment of choice and surgery is not required if it is diagnosed at an early stage. Conclusion: The diagnosis of abdominal tuberculosis still remains a challenge for both internists and surgeons. Before starting a therapy with adalimumab, every patient should be tested for latent tuberculosis infection.